Proceedings of the 10th International Conference on Agents and Artificial Intelligence 2018
DOI: 10.5220/0006656002110220
|View full text |Cite
|
Sign up to set email alerts
|

Social Emotion Mining Techniques for Facebook Posts Reaction Prediction

Abstract: As of February 2016 Facebook allows users to express their experienced emotions about a post by using five so-called 'reactions'. This research paper proposes and evaluates alternative methods for predicting these reactions to user posts on public pages of firms/companies (like supermarket chains). For this purpose, we collected posts (and their reactions) from Facebook pages of large supermarket chains and constructed a dataset which is available for other researches. In order to predict the distribution of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…They found that generally the emotional content of emojis and reactions correspond, but that in instances of sarcasm or politeness, the two channels could express different meanings. Krebs et al [29] used customer satisfaction data gathered from Facebook to train a model using convolutional and recurrent neural networks (CNN and RNN) and predict the reaction distribution for a given post. Basile et al [30] combine NLP and sentiment analysis of Facebook reactions to build a regression model that predicts news controversies in Italian media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that generally the emotional content of emojis and reactions correspond, but that in instances of sarcasm or politeness, the two channels could express different meanings. Krebs et al [29] used customer satisfaction data gathered from Facebook to train a model using convolutional and recurrent neural networks (CNN and RNN) and predict the reaction distribution for a given post. Basile et al [30] combine NLP and sentiment analysis of Facebook reactions to build a regression model that predicts news controversies in Italian media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes of proposed technique have greater precision compared with the existing techniques and also it could be applied for the estimation of micro scale market potential. Krebs et al (2017), proposed a reaction prediction on the Facebook post by using neural networks. For that, a data set was used to find the Facebook post reaction, and it was useful for both marketing users and machine learners.…”
Section: Day Et Al (2017)mentioning
confidence: 99%
“…ACM/IEEE, June 2019, Urbana-Champaign, Illinois USA © 2019 Association for Computing Machinery. the knowledge online platforms provide about human behavior-an area of research known as social-media analytics [3,6,9]. Studies in social-media analytics tend to focus either on text, using approaches such as Natural Language Processing (NLP), sentiment analysis, or opinion mining to arrive at and support research conclusions [12], or on the proliferation of content through online communities [5].…”
Section: Introductionmentioning
confidence: 99%